Bridging the gap-determinants of successful breastfeeding among mothers of rural India - Janardhan, Alok M.; Alok, Sandhya; Janardhan, Leelavathi; Sudhakar, Y. M. (International Journal Of Community Medicine And Public Health, 2020)
Background: Breastfeeding is the most crucial intervention with exponential positive impact on the maternal and infant health, that can change the community health outcome. Although a general awareness regarding breastfeeding cannot be undermined, there is significant gap in its optimal understanding, and practice in the rural community. Methods: Questionnaire-based cross-sectional study conducted in a rural nursing home and clinic. Mothers aged 15-45 years who were actively breast feeding or have breastfed in the past, visiting for various reasons. Results: Out of 300 mothers included in the study, most mothers were aged 20-30 years (66%), stay-at-home (77%), below-poverty-line (81%) with school-level education (43%). 77% mothers knew about breastfeeding initiation within 1 hour of life, 75% knew exclusive breastfeeding must be practiced for 6 months. 74% knew that breastmilk reduces risk of allergies in baby, 58% were aware of its thermoregulatory benefits in neonates, 41% knew about its contraceptive benefits. 17% mothers felt embarrassed to breastfeed in public, 28% felt breastfeeding is a hindrance to occupation. 51% mothers fed by partial emptying of both breasts in each feed, 28% practiced burping of children for 20 minutes, 5% stored expressed breastmilk at room temperature, none knew about storage of breastmilk in fridge. Conclusions: Mothers lack awareness about thermoregulatory benefits, reduced allergy risks and lactational contraceptive benefits of breastfeeding. They lag significantly, regarding complete emptying of each breast during feeds, adequate burping of baby, expression and storage of breastmilk. Significant gap between knowledge and practice of successful breastfeeding noted.